ANALISA CFD DAN AKTUAL PERFORMA TURBINE BULB DENGAN HEAD 0,6 METER - Gatot Eka Pramono (Department of Elektro Engineering, 2017)
Hydroelectric plant is the most widely used in Indonesia. Francis and pelton turbines are by far the most widely used type of turbine. Both are generally use the gravitational force of falling or flowing river. However, river flows is not only the potential of electricity, the power of ocean currents can also be used as a hydroelectric plant. One of the turbines is often used for the utilization of ocean currents is a bulb turbine nevertheless it can also be used in river flows. Bulb turbine test method is a way by varying the flow using CFD. CFD is a method to numerically calculate fluid flow by the control of dimensions, area and volume using computer. The results of testing using CFD by varying the flow of 300 l/s, 400 l/s and 454 l/s. A constant discharge of 300l/s produced 171 rpm rotation at a flow rate of 3.4 m/s, a constant discharge of 400l/s produced 1189 rpm rotation at a flow rate of 4.54 m/s, while a constant discharge of 454l/s produced 238 rpm at a flow rate of 5.15 m/s and obtained 2013W turbine power with turbine efficiency of 76% at 0.6 meters head in the flow of Katulampa tributary.